P119 Theory of Change Model for Clinic-Based PrEP Programme Evaluation. (30th June 2016) - Portman, Mags; Field, Nigel; Shahmanesh, Maryam; King, Carina; Brima, Nataliya; Saunders, John
Abstract : Background: A national programme to provide Truvada HIV pre-exposure prophylaxis (PrEP) is currently being considered in England. Some men already access PrEP and some sexual health clinics already offer PrEP monitoring. Aim(s)/objectives: We created a Theory of Change (ToC) to define the key components of a clinic-based PrEP programme to reduce HIV incidence. We identified indicators, outputs and outcomes to aid programme evaluation for a large London sexual health clinic. Methods: We used a ToC approach to define necessary pre-conditions, indicators, outputs and outcomes for our PrEP delivery programme. Results: The aim of our PrEP programme is to prevent HIV seroconversion in those at greatest risk. There are three broad areas: 1) identifying those eligible; 2) engaging eligibles to initiate PrEP and other HIV prevention activities; 3) maintaining effective adherence in those at continuing risk while advising therapy cessation for those no longer at risk. We estimate that approximately 1, 200 men attending our service annually could be eligible for PrEP. Assuming a high level of uptake, these men would require 1, 000 follow-up appointments annually in order to fulfil quality measures of three monthly HIV and STI testing in those on PrEP. Discussion: Using a ToC approach we have defined what a clinic-based PrEP programme might look like against our current service specification to enable us to collect meaningful evaluation data. This ToC might be used by other clinics to evaluate PrEP programmes, and allow comparison across programmes to build understanding of PrEP delivery and enhance new national PrEP surveillance systems.